Habitat-driven ecological strategies shape Chinese pine functional traits and rhizosphere metabolites in Qinling Mountains, China - Yang, Hang; Pang, Yue; Kang, Haibin; Song, Yahui; Hu, Kunlin; Wang, Yuchao; Wang, Dexiang (Frontiers in Plant Science, 2025)
AimsPlant functional traits (PFTs) and rhizosphere soil metabolites (RSMs) play crucial roles in the connection between plants and soil environments, influencing plant ecological adaptation processes. However, the strategies and driving factors underlying their variation in different habitats are poorly understood.MethodsIn this study, we investigated P.tabuliformis population traits and RSMs in two habitats, assessed trait and metabolite variations, and analyzed how traits and metabolites were associated with plant strategies.ResultsThe first principal component analysis (PCA) axis of the PFTs reflected trade-offs in traits linked to habitat: ridge habitat Chinese pine populations had high leaf dry matter content (LDMC) and fine root tissue density (FRTD) trait values that increased resource conservation, and slope habitat populations had high specific leaf area (SLA) and fine root specific root length (FRSRL) values that improved the efficiency of resource acquisition. The results of the metabolic pathway analysis of differential metabolites showed that in ridge habitats, adversity resistance-related metabolic pathways were significantly upregulated. Random forest model (RFM) analysis showed that the first PCA axis of PFTs and differential metabolites was significantly related to soil nitrogen and phosphorus content, indicating that soil nutrients are the primary factors driving the variation in P.tabuliformis population ecological adaptation strategies in different habitats.ConclusionsThus, the trade-offs between PFTs and the regulation of rhizosphere soil metabolism shape the population distribution of P.tabuliformis in different habitats. Along the terrain gradient, soil nutrients are the primary factors driving trait and metabolite regulation-based strategies.